Development of Meta-Geosystems of Tourist and Recreational Clusters - Anatoliy A. Yamashkin; Milan M. Radovanović; Stanislav A. Yamashkin; Marina A. Zhulina; Marko D. Petrović (Indonesian Journal of Geography, 2023)
The study aims to find a key to the problem of managing cultural heritage systems in the example of the Temnikov-Sanaksar cluster located in Eastern Europe. This area is situated between the forest-steppe of the layered-tier Volga upland and the forest geosystems of the layered Oka-Don lowland. The article applies an interdisciplinary approach to solving the problem of optimizing inter-component relationships in the meta-geosystems of tourist and recreational clusters. The sustainable development of meta-geosystems should be based on multifactorial information support, which implements the most important condition for the effective economic development of landscapes through the formation of the regions’ spatial data infrastructure. In order to consistently optimize meta-geosystems of different hierarchical levels, it is necessary to solve several emerging issues, such as assessing the strength and nature of inter-component connections in geosystems, determination of factors describing the territorial variation of the properties of geosystems, interpreting and substantiation the semantics of the selected basic factors.